Tourism Climate Change Adaptation: The Case of Slovenia - Turnšek, Maja; Cooper , Chris; Pavlakovič Farrell, Barbara; Kokot, Katja; Špindler, Tomi; Žnidaršič, Zala; Kuk , Rok; Pogačar, Tjaša (University of Maribor Press, 2024)
This monography is a result of the national research project “V7-2128 Climate change and sustainable tourism development in Slovenia”. It prepares the groundwork for adaptation within the tourism sector in Slovenia, assesses the risks and vulnerabilities of Slovenian tourism to climate change, and identifies possible adaptation options of Slovenian tourism. The analysis uses past climate data and three scenarios of climate change until the end of the 21st century. Two databases were used to get a wider range of available data: the Copernicus Climate Change Service and Slovenian Environment Agency archive data. The analysis focuses on four main areas of Slovenian tourism: (a) water related tourism, (b) urban and cultural tourism and MICE tourism, (c) winter outdoor tourism and (d) summer outdoor tourism. The results confirm past comparative research about Slovenian tourism being less vulnerable to climate change, with the important exception of winter tourism. While some of the climate change impacts are expected to even benefit Slovenian tourism, adaptation processes are still highly recommended both with regards to direct impacts, such as the increase of temperature, and indirect impacts such as the expected increase of tourism impacts on biodiversity due to the prolonged summer season.